If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2x + -5) = 100 Reorder the terms: 4(-5 + 2x) = 100 (-5 * 4 + 2x * 4) = 100 (-20 + 8x) = 100 Solving -20 + 8x = 100 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '20' to each side of the equation. -20 + 20 + 8x = 100 + 20 Combine like terms: -20 + 20 = 0 0 + 8x = 100 + 20 8x = 100 + 20 Combine like terms: 100 + 20 = 120 8x = 120 Divide each side by '8'. x = 15 Simplifying x = 15
| -17m-(-7m)=10 | | 10-2(4x+12)=-6x+4 | | 10-15y=-14y | | =123 | | 7r-2r=5 | | 9x-4=2(8+4x) | | 6(x+5)=-54 | | 3(r-10)=12 | | 8(x+4)=8(x+11) | | w+17=25 | | 11q=-14+12q | | -6y+13+9y=8y-3 | | x(-7)+7= | | 3n+14=2n | | 2y+2=-6x+4 | | 14c=13c+13 | | 2x+1-(4-x)=5x-2 | | 8c+-13c=-10 | | 6ab+3ax=3ab | | 8g=10g+8 | | 8=10-r | | -12+10(3+9r)=108 | | 3+2(3-1+2x)-3x= | | 7+8v+4=14 | | H=-9h-20 | | y-4+4=9+4 | | 7x-5x+4=26 | | 8x-21=-2x(x-7) | | -3(2x-4)-1=-25+6x | | -9x-1+4x+7=-4 | | x(x-7)*(-2)=1 | | x(x-7)*(-2)=0 |